Self-made myth : the poetic dialogue between Ted Hughes’s Birthday Letters and the poetry of Sylvia Plath in a selection of six poems - Lenahan, P. (University of Pretoria, 2021)
Dissertation (MA (English))--University of Pretoria, 2013.